Instrumental analysis of RNA modifications. (4th March 2021) - Yoluç, Yasemin; Ammann, Gregor; Barraud, Pierre; Jora, Manasses; Limbach, Patrick A.; Motorin, Yuri; Marchand, Virginie; Tisné, Carine; Borland, Kayla; Kellner, Stefanie
Abstract: Organisms from all domains of life invest a substantial amount of energy for the introduction of RNA modifications into nearly all transcripts studied to date. Instrumental analysis of RNA can focus on the modified residues and reveal the function of these epitranscriptomic marks. Here, we will review recent advances and breakthroughs achieved by NMR spectroscopy, sequencing, and mass spectrometry of the epitranscriptome. Graphical Abstract: UF0001